DEVELOPMENT OF ETHNOMATHEMATICS-BASED TEACHING MATERIALS USING KUE LUMPUR (MUD CAKE) ON FRACTION TOPICS TO IMPROVE NUMERACY AND SELF-EFFICACY OF FOURTH-GRADE STUDENTS - Aprillia Putri Pradinar; Wiryanto; Endah Budi Rahaju (SOSIOEDUKASI, 2026)
The low level of numeracy among fourth-grade primary school students in Indonesia remains a critical educational challenge that demands immediate and sustained attention. This study aims to develop ethnomathematics-based teaching materials using kue lumpur, a traditional Javanese mud cake, as a culturally familiar context for learning fractions, and to examine the feasibility, efficacy, and impact of these materials on student numeracy and self-efficacy. The study employed the ADDIE development model comprising five stages: Analysis, Design, Development, Implementation, and Evaluation. Implementation was conducted at SD Muhammadiyah 1-2 Taman Sidoarjo involving 20 fourth-grade students on February 10, 2026. Data were gathered through expert validation instruments, teacher response questionnaires, learning implementation observation sheets, numeracy tests (pretest and posttest), and a Likert-scale self-efficacy questionnaire. Due to non-normal distribution of posttest data confirmed by the Shapiro-Wilk test, the Wilcoxon signed-ranks test was applied for hypothesis testing. Results demonstrated that the developed materials received very high validity scores from material experts (4.86), media experts (5.0), and educational practitioners (5.0). Numeracy skills improved significantly, with mean scores increasing from 42.10 at pretest to 82.25 at posttest, yielding an N-Gain of 69.24% (moderate category) and a Wilcoxon significance value of 0.000. Students' self-efficacy reached a high category with a mean score of 75.75%, and 90% of students achieved high or very high self-efficacy ratings. These findings confirm that integrating local cultural contexts into mathematics instruction can substantially enhance both cognitive and affective dimensions of student learning.